Governing Sourcing Relationships. A Collection of Studies at the Country, Sector and Firm Level 8th Global Sourcing Workshop 2014, Val d'Isere, France, March 23-26, 2014, Revised Selected Papers - Kotlarsky, Julia; Oshri, Ilan.; Willcocks, Leslie P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book contains 11 papers from the 8th Workshop on Global Sourcing, held in Val d’Isère, France, during March 23–26, 2014, which were carefully reviewed and selected from 42 submissions. They are based on a vast empirical base brought together by leading researchers in information systems, strategic management, and operations. This volume is intended for students, academics, and practitioners interested in research results and experiences in outsourcing and offshoring of information technology and business processes. Topics discussed in this book combine theoretical and practical insights regarding challenges that industry leaders, policy makers, and professionals face; and they predominantly focus on how sourcing relationships are governed at the national, industry, and firm level. The contributions also examine current and future trends in outsourcing, paying particular attention to cloud services and their impact on the outsourcing sector.
Interculturality and Virtual Teams in IT Offshoring Context: A Social Regulation Theory Perspective -- Exploring IT Outsourcing Governance with Vendor’s Interpersonal Networks: A Case Study -- Cloud Challenges for an ERP Vendor: Business Model Implications -- How Collaboration Software Enables Globally Distributed Software Development Teams to Become Agile - An Effective Use Perspective -- Fit in Cloud Sourcing Arrangements: An Ontological Perspective -- Governance of Multivendor Outsourcing Arrangements: A Coordination and Resource Dependency View -- Capturing CSR: Doing Good Offshore -- Reframing Outsourcing Through Social Networks: Evidence from Infocert’s Case Study -- Transformation in the Dutch Non-life B2C Insurance Sector: Sourcing Implications -- On the Attractiveness of the UK for Outsourcing Services -- Global Service Market Trends in Hungarian Shared Service Centers.
Keywords: Management information systems; Computer science; Organization; Planning; Computer industry; Industrial procurement; Management of Computing and Information Systems; Organization; The Computer Industry; Procurement